2014
DOI: 10.1159/000354990
|View full text |Cite
|
Sign up to set email alerts
|

NR5A1 Gene Mutations: Clinical, Endocrine and Genetic Features in Two Girls with 46,XY Disorder of Sex Development

Abstract: Background: Steroidogenic factor 1, encoded by the NR5A1 gene, is a key regulator of endocrine function within the hypothalamic-pituitary-steroidogenic axis. Both homozygous, compound heterozygous and heterozygous mutations in the NR5A1 gene may determine 46,XY disorders of sex development (DSD). Patients and Methods:NR5A1 gene sequencing was performed in a cohort of 6 patients with 46,XY DSD without specific diagnosis. Results: Heterozygous NR5A1 gene mutations were found in 2 girls, aged 0.5 years and 14 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Annotation and filtering of variants were performed with Variant Interpreter platform; the NGS coverage was analyzed in detail using Integrative Genome Viewer version 2.3. Variants and regions with a depth coverage below 50× were confirmed by Sanger sequencing using previously described procedures [Bertelloni et al, 2014] and were checked for previously reported causative mutations in published works and variant databases: Human Gene Mutation Database (HGMD) and Leiden Open Variation Database (LOVD). Variants were classified following the American College of Medical Genetics (ACMG) and genomics recommendations [Richards et al, 2015] using population frequency databases (dbSNP, ExAC, GnomAD exomes, and GnomAD genomes) and in silico tools including PolyPhen, SIFT, Align GVGD, DANN, FATHMM, Mutation Assessor, and Muta-tionTaster.…”
Section: Methodsmentioning
confidence: 99%
“…Annotation and filtering of variants were performed with Variant Interpreter platform; the NGS coverage was analyzed in detail using Integrative Genome Viewer version 2.3. Variants and regions with a depth coverage below 50× were confirmed by Sanger sequencing using previously described procedures [Bertelloni et al, 2014] and were checked for previously reported causative mutations in published works and variant databases: Human Gene Mutation Database (HGMD) and Leiden Open Variation Database (LOVD). Variants were classified following the American College of Medical Genetics (ACMG) and genomics recommendations [Richards et al, 2015] using population frequency databases (dbSNP, ExAC, GnomAD exomes, and GnomAD genomes) and in silico tools including PolyPhen, SIFT, Align GVGD, DANN, FATHMM, Mutation Assessor, and Muta-tionTaster.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of NR5A1 mutations were described in 46,XY DSD patients. The phenotypical spectrum encompasses hypospadias [1012], ambiguous genitalia like a hypoplastic phallus [1315], or a complete external female appearance [1619], but also only male infertility [2022]. Furthermore, NR5A1 mutations were found in 46,XX patients with premature ovarian failure and primary ovarian insufficiency [17, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three independent groups identified also a recurrent NR5A1 p.R92W mutation in several patients with 46,XX testicular/ ovotesticular DSD, highlighting the role of NR5A1 in the development of both testes and ovaries [2527]. Except for five reported cases with adrenal insufficiency [2832] and some patients with mild elevated ATCH [16, 33] most NR5A1 mutations were described in 46,XY DSD patients with normal adrenal function at the date of examination.…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, more than 25% of the females referred to our departments with clinical/endocrine diagnosis of CAIS did not have this diagnosis confirmed by genetic analysis [20]. …”
mentioning
confidence: 99%